Sports events and community development: Analysis of the AFCON 2022 host cities in Cameroon - Paul Nkemngu Acha-Anyi (Cogent Social Sciences)
The study presents an analysis of development opportunities presented by the African Cup of Nations (AFCON) tournament that was held in Cameroon from 6 January to 9 February 2022, as perceived by residents of the host cities. A quantitative research paradigm was employed through the use of a structured questionnaire. Data were collected from a total of 1683 respondents from all five host cities during the competition. A key finding from this study is that respondents were quite optimistic about the development opportunities presented by the sports event, particularly with regard to the promotion of their city as an attractive destination. Through the lens of the Social Representation Theory, the influence of the political and cultural backgrounds of some the respondents was also found from the data collected. The case of cultural representation was observed in the case where very few women participated in the Muslim-dominated North Region, while the social tensions in the Southwest region could be said to explain why respondents from Limbe presented the least optimistic views. The practical and policy implications of the study are elaborated on, including the need for government and sports event organisers to include community representatives as part of the planning and delivery committee. The original contribution of this study spans from the analysis of data from five host cities, through to the meaningful application of the SRT, to the unique socio-political context of Cameroon.